THE ENHANCEMENT OF METHODOLOGY IN THE MODERN EDUCATION - Urinova Nodira (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The methodology is a method of joint activity of teachers and students aimed at solving educational problems. Acceptance is an integral part or a separate aspect of the method. Individual techniques can be part of different methods. For example, recording of basic concepts by students is used by the teacher when explaining new material, working independently with the original source. Methods and techniques are used in various combinations during the learning process. In this article, the impact of modern methods on the development of the educational system and modern methods are discussed.